Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Get immediate and reliable answers to your questions from a community of experienced professionals on our platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To solve the system of linear equations given by:
[tex]\[ \begin{array}{l} y = 4x + 3 \\ y = -x - 2 \end{array} \][/tex]
we need to find the values of [tex]\(x\)[/tex] and [tex]\(y\)[/tex] that satisfy both equations simultaneously.
1. Step 1: Set the right-hand sides of the equations equal to each other because they both equal [tex]\(y\)[/tex].
[tex]\[ 4x + 3 = -x - 2 \][/tex]
2. Step 2: Solve for [tex]\(x\)[/tex].
First, add [tex]\(x\)[/tex] to both sides to get:
[tex]\[ 4x + x + 3 = -2 \][/tex]
which simplifies to:
[tex]\[ 5x + 3 = -2 \][/tex]
Next, subtract 3 from both sides:
[tex]\[ 5x = -2 - 3 \][/tex]
which simplifies to:
[tex]\[ 5x = -5 \][/tex]
Finally, divide both sides by 5 to isolate [tex]\(x\)[/tex]:
[tex]\[ x = -1 \][/tex]
3. Step 3: Substitute the value of [tex]\(x\)[/tex] back into one of the original equations to solve for [tex]\(y\)[/tex]. We'll use the first equation [tex]\(y = 4x + 3\)[/tex]:
[tex]\[ y = 4(-1) + 3 \][/tex]
which simplifies to:
[tex]\[ y = -4 + 3 \][/tex]
[tex]\[ y = -1 \][/tex]
So, the solution to the system of equations is:
[tex]\[ (x, y) = (-1, -1) \][/tex]
[tex]\[ \begin{array}{l} y = 4x + 3 \\ y = -x - 2 \end{array} \][/tex]
we need to find the values of [tex]\(x\)[/tex] and [tex]\(y\)[/tex] that satisfy both equations simultaneously.
1. Step 1: Set the right-hand sides of the equations equal to each other because they both equal [tex]\(y\)[/tex].
[tex]\[ 4x + 3 = -x - 2 \][/tex]
2. Step 2: Solve for [tex]\(x\)[/tex].
First, add [tex]\(x\)[/tex] to both sides to get:
[tex]\[ 4x + x + 3 = -2 \][/tex]
which simplifies to:
[tex]\[ 5x + 3 = -2 \][/tex]
Next, subtract 3 from both sides:
[tex]\[ 5x = -2 - 3 \][/tex]
which simplifies to:
[tex]\[ 5x = -5 \][/tex]
Finally, divide both sides by 5 to isolate [tex]\(x\)[/tex]:
[tex]\[ x = -1 \][/tex]
3. Step 3: Substitute the value of [tex]\(x\)[/tex] back into one of the original equations to solve for [tex]\(y\)[/tex]. We'll use the first equation [tex]\(y = 4x + 3\)[/tex]:
[tex]\[ y = 4(-1) + 3 \][/tex]
which simplifies to:
[tex]\[ y = -4 + 3 \][/tex]
[tex]\[ y = -1 \][/tex]
So, the solution to the system of equations is:
[tex]\[ (x, y) = (-1, -1) \][/tex]
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.